Qualidade da água em Ribeirópolis-SE : o açude do Cajueiro e a barragem do João Ferreira - Lima, Wesley Santos (2008)
The currente work has as purpose to evaluate the quality of Cajueiro s dam water and João Ferreira s dyke, situated in peripheral zones of Ribeirópolis Sergipe - Brazil, important area of growing of vegetables and fishing. Projected by DNOCS and CODEVASF, respectively, to provide water for the country region, decreasing the drought s impacts in the region, it encounters at present in advanced condition of atropism, owing to bad use of their waters and disordered occupation of the soil. The problematic site s diu mainly to the fusion of household drains. Aiming at evaluating the dimension of that problem, two campaigns were carried out in six different points of the dam and the dike, being determined physical parameters (turbine, electric conductivity, temperature, totally dissolved solids, transparency), and chemical ones (pH, dissolved oxygen, hardness, nutrients, chlorides and metals) and biological ones (total and fece s bacteria). The analytical procedures are according to APHA (1998). The collections were carried out in the rainy weather (april/2007) and in the drought (february/2008). The results of the physical and chemical and bacterium s parameters reveal that the dam s water is unfit for human consumption and seaside resort, being featured from class 2, according to CONAMA s resolution n° 357/05. Besides, it s unfit for irrigation, due to the high charge of bacteria and salt ness. Already the dike s water possesses a smaller quantity of bacteria, however, needing cares regarding the launch of agriculture s defensive. Those results show the need of measures in the meaning of implementing improvements of sanitary order that play down the pollution of the dam s and dyke s waters and consequently the environmental quality of the population that use its waters.